Aristotle and Hamilton on commerce and statesmanship - Chan, Michael D., 1968- (University of Missouri Press, 2006)
"Examines Alexander Hamilton's political economy in relation to Aristotle's classical views of economics, as presented in his Politics, and finds shared support of commerce in pursuit of a regime's or democracy's wider goals"--Provided by publisher.